Evolution of Keratoconus: From Diagnosis to Therapeutics - Imbornoni, Lauren Marie; McGhee, Charles Ninian John; Belin, Michael Wellington (Klinische Monatsblätter für Augenheilkunde, 2018)
This review describes the evolution of the diagnosis and treatment of keratoconus from the earliest written description to present day. The first description was provided in 1736 by Benedict Duddell who described the prominent corneas of a fourteen-year-old boy. Throughout the 19th century, a variety of surgical procedures were proposed to manage the disease, such as surgically repositioning the pupil away from the cone, iris incarceration to produce a slit-like pupil, cauterization of the cone to produce a scar, and full thickness elliptical excision of the cone. Despite the ingenuity of these procedures, many led to serious complications. In 1936, Ramon Castroviejo revolutionized surgical management by performing the first corneal transplant for keratoconus. The advent of refractive surgery in the 1990s brought about a sudden and critical need for better understanding of keratoconus and corneal ectatic disease. Topographic analysis allowed for earlier detection of keratoconus, prior to clinical signs and symptoms. Tomographic analysis provided analysis of the anterior and posterior surfaces of the cornea and allowed for even earlier detection. The Belin/Ambrosio Enhanced Ectasia Display on the Pentacam incorporates anterior and posterior elevation, pachymetric map, best fit sphere and enhanced reference surface to provide an overall “D” value that is predictive of ectatic disease. This display allows refractive providers to quickly and accurately screen potential refractive surgery candidates to identify those at risk for ectasia and early subclinical keratoconus. Corneal crosslinking was revolutionary in the treatment of keratoconus. There have been several randomized controlled trials that have found it to be safe and effective to halt ectatic progression. Crosslinking was recently approved by the FDA for progressive keratoconus. Currently, there is no clear definition of ectasia progression. Providers must be able to clearly, objectively and consistently diagnose progressive disease to institute timely treatment in the population with the greatest potential benefit. The new Belin ABCD grading system and progression analysis incorporated into the Oculus Pentacam software provides an objective way of assessing progression over time. Keratoconus diagnosis and management have grown tremendously since the first description in 1736, but there is still much to learn about keratoconus and its management.
Keywords: cornea; history of medicine; refractive surgery